PbO-GeO2 rib waveguides for photonic applications - Del Cacho, V. D.; da Silva, D. M.; Kassab, L. R P [UNESP]; Siarkowski, A. L.; Morimoto, N. I. (Elsevier B.V. Sa, 2011)
This work presents for the first time to our knowledge the fabrication and characterization of rib waveguides produced with PbO-GeO2 (PGO) thin films. The target was manufactured using pure oxides ( 60 PbO-40 GeO2, in wt%) and amorphous thin films were produced with the RF sputtering technique. PGO thin films present small absorption in the visible and in the near infrared and refractive index of similar to 2.0. The definition of the rib waveguide structure was made using conventional optical lithography followed by plasma etching, performed in a Reactive Ion Etching (RIE) reactor. Light propagation mode in the waveguide structure was analyzed using integrated optic simulation software. Optical loss measurements were performed to determine the propagation loss at 633 nm, for ribs with height of 70 nm and width of 3-5 mu m; experimental values around 2 dB/cm were found for the propagation loss and confirmed the theoretical calculations. The results obtained demonstrate that PGO thin films are potential candidates for application in integrated optics. Published by Elsevier B.V.
Keywords: Thin film; Germanate; Waveguide; Sputtering; Photonic